2019
DOI: 10.3126/njb.v6i1.22330
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Growth Statistics of Two Species of Paulownia and Optimization of Rooting Methods

Abstract: Paulownia is a fast-growing woody tree, native to the forests of China. It belongs to the family Scrophulariaceae and is mainly used as a source of wood for furniture and musical instruments. Due to its fast-growing nature and high-quality of wood, there has been growing interest in cultivation and research of Paulownia in Nepal. Growth comparison was performed by measuring shoot length in in vitro condition. Among two species of Paulownia - Paulownia tomentosa (Thunb.) Steud and Paulownia fortuneii (Seem.) He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Rooting experiment was carried out in this study using two auxins combined, as well as some of the treatments separately with other literature such as Shiragave [71] who reported that the efficiency of IBA than other auxins in rooting in Phyllanthus reticulatus. Also, Paulownia tomentosa and Paulownia fortuneii had the longest root and density when Saiju et al [72] employed MS medium with NAA at (0.5 or 1.5 mg/l) in the growing medium. Furthermore, the number of almond peach rootstock hybrids has grown on MS medium containing IBA [73].…”
Section: Discussionmentioning
confidence: 99%
“…Rooting experiment was carried out in this study using two auxins combined, as well as some of the treatments separately with other literature such as Shiragave [71] who reported that the efficiency of IBA than other auxins in rooting in Phyllanthus reticulatus. Also, Paulownia tomentosa and Paulownia fortuneii had the longest root and density when Saiju et al [72] employed MS medium with NAA at (0.5 or 1.5 mg/l) in the growing medium. Furthermore, the number of almond peach rootstock hybrids has grown on MS medium containing IBA [73].…”
Section: Discussionmentioning
confidence: 99%